Connecting Universiti Sains Malaysia Art Scholars with Open Access Publication - Ahmat, Muhammad Akmal (2015)
In Universiti Sains Malaysia (USM), the scholars were known to publish their scholarly materials in commercial journals, magazines, and books. However, studies on trends of publishing in Open Access journals, self archive in institutional repositories (IRs) and Open Access perceptions among art scholars are still enigmatic. For these reasons, the USM librarians have established a research team that focused on studying the Open Access publication trend. Next, the team intended to develop an effective approach in advocating Open Access publication targeting specific groups of researchers, especially the art scholars. The Open Access team had persuaded art scholars to organize a pilot study through a focus group meeting. The focus group meeting was held at the School of Art, USM on 2nd September 2014. During the meeting, the librarians and the art scholars discussed on the Open Access issues. The librarians presented the pros and cons of the Open Access and the art scholars gave responded to the USM librarians’ presentation. Based on the feedback, the effective approach to advocate Open Access, specifically for art scholars were identified.This paper is significant as a guide for the librarians that intend to advocate the Open Access publication.